2002
DOI: 10.1614/0890-037x(2002)016[0833:cvahai]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Carrier Volume Affects Herbicide Activity in Simulated Spray Drift Studies1

Abstract: Field studies were conducted to determine if varying carrier volume proportionally with herbicide dosage, thus maintaining constant herbicide concentration in the carrier, would change the response of sweet corn to glyphosate and of cotton to 2,4-D when compared with using a constant carrier volume where herbicide concentration would vary and be more dilute. For all the parameters measured, more sweet corn injury occurred if the concentration of glyphosate was constant in all volumes of spray. The glyphosate n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
61
1
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(67 citation statements)
references
References 20 publications
4
61
1
1
Order By: Relevance
“…In 2010, grain sorghum yield was reduced 73% when applied in the constant carrier volume of 224 L ha À1 compared to a yield reduction of 55% when applied in the proportional carrier volume averaged across 56, 28, and 14 L ha À1 . These data are in contrast to those previously reported for 2,4-D on cotton (Gossypium hirsutum L.) and for glyphosate on sweet corn (Zea mays L.) (Banks and Schroeder 2002) and for glyphosate on corn (Ellis et al 2002) and for glyphosate on wheat (Triticum aestivum L.) (Roider et al 2008). A possible explanation for this is the number of droplets deposited on the grain sorghum leaves.…”
Section: Resultscontrasting
confidence: 98%
See 1 more Smart Citation
“…In 2010, grain sorghum yield was reduced 73% when applied in the constant carrier volume of 224 L ha À1 compared to a yield reduction of 55% when applied in the proportional carrier volume averaged across 56, 28, and 14 L ha À1 . These data are in contrast to those previously reported for 2,4-D on cotton (Gossypium hirsutum L.) and for glyphosate on sweet corn (Zea mays L.) (Banks and Schroeder 2002) and for glyphosate on corn (Ellis et al 2002) and for glyphosate on wheat (Triticum aestivum L.) (Roider et al 2008). A possible explanation for this is the number of droplets deposited on the grain sorghum leaves.…”
Section: Resultscontrasting
confidence: 98%
“…These results showing greater yield reduction in 2012 are likely attributable to reduced rainfall during the growing season (Table 1), perhaps due to decreased herbicide metabolism as the plants adjusted to drier conditions. The increased yield reduction from the proportional carrier volumes agree with results reported for glyphosate (Banks and Schroeder 2002;Ellis et al 2002;Roider et al 2008) but disagrees with 2010 results. A possible explanation could be increased epicuticular wax loads on grain sorghum plants in 2012.…”
Section: Resultssupporting
confidence: 49%
“…The reason for selecting this particular methodology for herbicide application was to avoid the potential underestimation of herbicide efficacy by applying dilute concentration of herbicide in a large carrier volume. Previous research dealing with simulated drift has suggested that in addition to the amount of herbicide delivered, the droplet size and the concentration of the herbicide solution should ideally be held in the same proportion as it would have been applied to the original target field (Banks and Schroeder 2000). Spray volume and concentration have been studied for both paraquat (McKinlay et al 1974) and glyphosate (Cranmer and Linscott 1990;Ellis et al 2001).…”
Section: Methodsmentioning
confidence: 99%
“…Derivas acidentais durante a aplicação têm potencial para provocar danos em cultivos no sistema de semeadura direta (Hemphill Jr. & Montgomery, 1981;Gelmini, 1988;Ramsdale & Messersmith, 2001;Banks & Schroeder, 2002;Lyon et al, 2003b) e no algodoeiro Lyon et al, 2003a;Miller et al, 2004), fazendo-se necessário gerar informações para a caracterização e quantificação desses efeitos. Também, a possibilidade de uso de cultivares de algodão, soja e milho geneticamente modificados para resistência ao herbicida glyphosate deverá aumentar o potencial de deriva desse produto para culturas/cultivares sensíveis.…”
Section: Introductionunclassified